Engineering psychology and cognitive ergonomics : 16th international conference, EPCE 2019, held as part of the 21st HCI international conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings /: 16th international conference, EPCE 2019, held as part of the 21st HCI international conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings. (2019) - Unknown
No abstract available